A Comparative Perspective of the National Innovation Systems in Europe - Toshevska-Trpchevska, Katerina; Makrevska-Disoska, Elena; Stojkoski, Viktor; Tevdovski, Dragn (Senate Hall, 2020)
This paper provides empirical evidence on the innovation performance in European countries in the period 2012-2014 based on a micro level analysis. We provide a comparative perspective among three different institutional settings in Europe: Central and Eastern European countries (CEE), Southern European countries and Northern European countries. We estimate the CDM model of simultaneous equations while using data from the Eurostat Community Innovation Survey 2014 (CIS2014). This model directly links R&D engagement and intensity to innovation outcomes measured either as process or as product innovation and then estimates the effectiveness of the innovative efforts in terms of productivity gains. In general, during our observation period, which fell in the aftermath of the 2008 financial crisis, the links between innovation inputs, innovation outputs and productivity were found to be rather weak. Another remarkable finding from our study is that, notwithstanding a higher participation in innovation by larger firms, among those firms that innovate, innovation output is relatively higher for small firms (compared to large firms) in Northern Europe. This relatively important role for small firms in innovation was not found for the other two country groups.
Keywords: innovation system|productivity|CDM model|European countries|CIS2014